2023
DOI: 10.1186/s12917-023-03810-1
|View full text |Cite
|
Sign up to set email alerts
|

Persea americana extract protects intestinal tissue from Eimeria papillata-induced murine Infection

Fatemah Alajmi,
Tahani Al-Otaibi,
Saleh Al-Quraishy
et al.

Abstract: Coccidiosis is the most prevalent disease-causing widespread economic loss among farm and domestic animals. Currently, several drugs are available for the control of this disease but resistance has been confirmed for all of them. There is an urgent need, therefore, for the identification of new sources as alternative treatments to control coccidiosis. The present work aimed to study the effect of the Persea americana extract (PAE) as an anti-coccidial, anti-oxidant, and anti-apoptotic modulator during murine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…These oxidative indicators play an important role in protecting the animal body from free radical damage due to increased accumulation of reactive oxygen species (ROS) during Eimeria infection. Previous research has found that Eimeria infection disrupts the antioxidant defense system, resulting in detrimental cellular effects (10,(50)(51)(52)(53)(54). In this study, KLRE significantly prevented Eimeria infection-induced loss of these markers (CAT and SOD) and increased their activity, which is consistent with Carini et al (55) for free radical scavenging properties that protect against oxidative damage and get rid of excess peroxides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These oxidative indicators play an important role in protecting the animal body from free radical damage due to increased accumulation of reactive oxygen species (ROS) during Eimeria infection. Previous research has found that Eimeria infection disrupts the antioxidant defense system, resulting in detrimental cellular effects (10,(50)(51)(52)(53)(54). In this study, KLRE significantly prevented Eimeria infection-induced loss of these markers (CAT and SOD) and increased their activity, which is consistent with Carini et al (55) for free radical scavenging properties that protect against oxidative damage and get rid of excess peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Effective management of coccidiosis relies on vaccination and the use of chemoprophylaxis. However, the widespread and excessive use of synthetic coccidiostats has led to the development of drug resistance among various parasites (5)(6)(7)(8)(9)(10). Consequently, alternative strategies for coccidiosis control have rapidly emerged and developed in response to these challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Coccidiosis continues as one of the most destructive protozoan diseases of wild and domestic animals worldwide and causing economic losses ( 1 ). The causative agent for this disease is the host-specific apicomplexan species belonging to the genus Eimeria (Eucoccidiorida, Eimeriidae) which is transmitted via the fecal-oral route of oocysts, which release infectious sporozoites in the intestine ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mucus layer coating the gastrointestinal tract is considered the front line of innate host defense, largely because of the secretory products of intestinal goblet cells, including the mucin MUC2 ( 4 ). Indeed, Eimeria infection has been associated with an increase in the incidence of pathological conditions, inflammation, and oxidative stress that affects the general body performance ( 1 ).…”
Section: Introductionmentioning
confidence: 99%